21. Habituation of somatosensory evoked potentials in patients with dementia. Issue 12 (December 2016) - Gorini, M.; Tanzilli, A.; Cardillo, A.; Greco, D.; Rinalduzzi, S.; Pierelli, F.; Fattapposta, F.; Trompetto, C.; Currà, A.
Abstract : Habituation is defined as "a response decrement with repeated stimulation". In normal cerebral cortex repetitive stimulation delivered with various sensory modalities elicits responses characterized by habituation, presumably owing to mechanisms that alter synaptic effectiveness. Habituation may represent an early, pre-clinical marker of synaptic dysfunction. In dementia, evidence of changes in synaptic functioning in sensory cortices is lacking. We investigated somatosensory evoked potentials (SEPs) habituation in 29 patients with mild dementia, grouped according to clinical, neuropsychological, and neuroimaging features. We recorded median-nerve SEPs in 15 AD-type and 14 VD-type, mild dementia, and 15 controls. We measured N20-P25 amplitudes from 3 blocks of 200 sweeps, and assessed amplitude of block 1, and habituation from amplitude changes between the 3 sequential blocks. ANOVA showed a main effect of factor group ( F  = 3.43 p  = 0.042). AD-type patients, had normal block1 SEP amplitudes, but abnormal habituation ( p  = 0.036). VD-type patients had normal SEP amplitudes and habituation ( p  = 0.58). SEP habituation is altered in AD-type dementia suggesting hyperresponsivity of the somatosensory cortex. This abnormality is not found in patients with VD-type mild dementia, which manifest normal synaptic function to repetitive stimulation. Further investigation is deserved to see whether abnormal SEP habituation may represent a neurophysiological marker of degenerative dementia.